Sol-Gel Synthesis and Electrical Characterization of Li1+xAlxTi2-x(PO4)3 Solid Electrolytes - Kimpa, Mohammed Isah; Mayzan, Mohd Zul Hilmi; Esa, Fahmiruddin; Yabagi, Jibrin Alhaji; Muhammad Nmaya, Muhammad; Agam, Mohd Arif (Journal of Science and Technology, 2017)
This composition of Lithium Aluminium Titanium Phosphate (LATP) has potential for the fast growing energy storage to be used as solid electrolyte in Li-ion battery. This material is required to solve safety problems of current lithium ion battery. In this study, Li1+xAlxTi2-x(PO4)3 (x = 0.0, 0.1 and 0.2) nanocrystalline composition were synthesized by sol gel method. Lithium Nitrate (LiNO3), Aluminium Nitrate Nonahydrate (Al(NO3)3.9H2O), Titanium (IV) Butoxide (Ti(OC4H9)4) and Ammonium dihydrogen phosphate (NH4H2PO4) were used as starting materials. Citric acid monohydrate was used to control the pH value and ethylene glycol was used as solvent during the preparation. Pure NASICON-type powder with rhombohydral structure (R-3c) space group were obtained after heating the gel precursor at 950 Â°C for 5 h. The resulting materials were characterized using X-ray diffraction (XRD) and field emission scanning electron microscopy (FESEM). The Ionic conductivity of the polished samples was carried out using AGILENT 4294A precision impedance analyzer. The XRD analysis revealed pure crystalline phase of LiTi2(PO4)3 NASICON structure with minor impurities (TiO2 and TiP2O7). The highest ionic conductivity value was found approximately 7.936Ã—10-4 S cm-1 for Li1.2Al0.2Ti1.8(PO4)3 sample. It can be summarized that sol-gel method is more promising compared to traditional solid-state method.